Analisa Penempatan Kamera CCTV Menggunakan Metode Simple Additive Weighting (SAW) Untuk Smart Monitoring - Widodo, Gianto; ., Rahmadwati; Santoso, Purnomo Budi; Kurniawan, Fachrul (MATICS, 2016)
Abstract-monitoring technology is an area or region now isgrowing rapidly, this refers to the interest to be used.Closed Circuit Television (CCTV) is a type of camera thatwas used for the supervisor of the building or room, but itcan also be used to monitor the condition of congestion androad conditions. The problems are the installation ofCCTV is not always right on target because it is onlyinstalled for trend following, without looking at theconditions that will be installed, so it becomes less thanoptimal. Many of the problems in need of supervision bythe Government. Problems such as road density, accidentprone area, business area, area schools, parking area andpopulation density at the location of the road is a problemthat requires supervision. In order for the supervision canbe done with the optimal technological devices are usedthen the information and communication technology, theutilization for surveillance of a region commonly referredto with the Smart Monitoring, the device that can be usedis CCTV. In order to target the right CCTV installationrequires a calculation and analysis of the right against theconditions of the point to be fitted, to allow the installationof CCTV can be right on target and not just follow thetrend of development of the technology. Many of theproblems that have to be analyzed before the installationof CCTV, to find the solution of many problems, thisresearch using methods MCDM method Simple AdditiveWeighting (SAW). Based on the results of the calculationof 40 data points of observation in the city of XYZ with 10categories, problems and preferences 3 weights usedproduce a value Vi maximum 4 point, and that point isrecommended for CCTV installed.Keywords: SAW, CCTV